Intussusception in a Goat Kid - A Case Report - Subramaniyan, Muthukumar; Vanan, Thanga Thamil; Subramanian, Meenakshi Sundaram; Senthilnayagam, Hemalatha (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A study was carried out to find out the various causes of mortality in goat kids and to optimize the management strategies to control kid mortality in an organized goat farm with more than 500 breedable Tellicherry does in Kancheepuram district, Tamil Nadu, India. Detailed necropsy was carried out in all 52 kids were died out of 551 live kids born during the study period (July-Mar) of nine months. The various factors identified for the kid mortality were low birth weight (8.57%), pneumonia (4.29%), navel ill (2.86%), cystic calculi (2.86%), roundworm infestation (1.43%) and brain suppurative encephalitis (1.43%) to the total mortality. Further, An interesting case of Intussusception of the intestine was found to be the noticeable cause of death at this farm. This contributed nearly to 2.86% of the total goat kid loss during the study period. This might be due to hypermotility of the intestine with multi-factorial origin.